Time-domain analysis of intermodulation distortion of closed-loop Class D amplifiers - Yu, J.; Tan, M.T.; Cox, Stephen M.; Goh, W.L. (IEEE, 2012)
This paper presents a time-domain analysis of the intermodulation distortion (IMD) of a closed-loop Class D amplifier with either 1st-order or 2nd-order loop filter. The derived expression for the IMD indicates that there exist significant 3rd-order intermodulation products (3rd-IMPs) within the output spectrum, which may lead to even greater distortion than the intrinsic harmonic components. In addition, the output expressions are compact, precise and suitable for hand calculation, so that the parametric relationships between the IMD and the magnitude and frequency of the input signals, as well as the effect of the loop filter design, are straightforwardly investigated. In order to accurately represent the IMD performance of Class D amplifiers, a modified testing setup is introduced to account for the dominantly large 3rd-IMPs when the ITU-R standard is applied.